Emigration from China to the West Indies - White, James T.; Great Britain Colonial Office; National Archives (Great Britain); Adam Matthew Digital (Adam Matthew Digital, 1851)
Colonial Office file containing correspondence to and from James T. White in Hong Kong, agreements and other documents concerning the recruitment of Chinese emigrants to work as labourers in the British West Indies